Habitus Moderasi Beragama di Desa Besowo Kabupaten Kediri: Perspektif Fenomenologi - Moh. Irmawan Jauhari; A. Jauhar Fuad; Muhammad Akmal Auli; Istiqomah (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2024)
This article aims to analyze the local value of moderate attitudes and the habituation process of moderate attitudes based on social space in Besowo Kepung Kediri. This research uses a qualitative approach with a phenomenological type to explore data related to the habitus model at the research location. Data was obtained through observations and interviews in the field as well as supporting documentation. Where data sources through informants were taken from some Besowo residents who were considered knowledgeable and competent to answer research questions including community leaders, religious leaders and village government. The analysis was carried out in three simultaneous stages, namely, condensation, verification and data presentation. The research results state: 1) Local values ​​of moderate attitudes that exist at the research location include tolerance, compassion, willingness to accept other people's religions, gentleness in religious activities, and justice. These local values ​​are applied well so that the community has a high awareness of the importance of caring for diversity so that cultural immunity emerges. 2) The process of habituation to a moderate attitude receives a response and support from religious leaders, stakeholders, and the village government. Everyone is active in habituating moderate attitudes to direct society to adopt cultural values ​​that support moderate attitudes. Habituation is strengthened by the behavior of religious communities who support each other with policy makers to create conduciveness.